(2x+4)(x+4)=196+3x

Simple and best practice solution for (2x+4)(x+4)=196+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+4)(x+4)=196+3x equation:


Simplifying
(2x + 4)(x + 4) = 196 + 3x

Reorder the terms:
(4 + 2x)(x + 4) = 196 + 3x

Reorder the terms:
(4 + 2x)(4 + x) = 196 + 3x

Multiply (4 + 2x) * (4 + x)
(4(4 + x) + 2x * (4 + x)) = 196 + 3x
((4 * 4 + x * 4) + 2x * (4 + x)) = 196 + 3x
((16 + 4x) + 2x * (4 + x)) = 196 + 3x
(16 + 4x + (4 * 2x + x * 2x)) = 196 + 3x
(16 + 4x + (8x + 2x2)) = 196 + 3x

Combine like terms: 4x + 8x = 12x
(16 + 12x + 2x2) = 196 + 3x

Solving
16 + 12x + 2x2 = 196 + 3x

Solving for variable 'x'.

Reorder the terms:
16 + -196 + 12x + -3x + 2x2 = 196 + 3x + -196 + -3x

Combine like terms: 16 + -196 = -180
-180 + 12x + -3x + 2x2 = 196 + 3x + -196 + -3x

Combine like terms: 12x + -3x = 9x
-180 + 9x + 2x2 = 196 + 3x + -196 + -3x

Reorder the terms:
-180 + 9x + 2x2 = 196 + -196 + 3x + -3x

Combine like terms: 196 + -196 = 0
-180 + 9x + 2x2 = 0 + 3x + -3x
-180 + 9x + 2x2 = 3x + -3x

Combine like terms: 3x + -3x = 0
-180 + 9x + 2x2 = 0

Factor a trinomial.
(-12 + -1x)(15 + -2x) = 0

Subproblem 1

Set the factor '(-12 + -1x)' equal to zero and attempt to solve: Simplifying -12 + -1x = 0 Solving -12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -1x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = 0 + 12 -1x = 0 + 12 Combine like terms: 0 + 12 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12

Subproblem 2

Set the factor '(15 + -2x)' equal to zero and attempt to solve: Simplifying 15 + -2x = 0 Solving 15 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -2x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = 0 + -15 -2x = 0 + -15 Combine like terms: 0 + -15 = -15 -2x = -15 Divide each side by '-2'. x = 7.5 Simplifying x = 7.5

Solution

x = {-12, 7.5}

See similar equations:

| 10m+6=6m+30 | | x-15=x/77 | | -4p-12=12 | | w+2.9=6.4 | | z^2=-2z-14 | | -3/8t=1/6 | | y=20-3(1) | | g=y-cx | | 8(3n+3)=8(6n+3)+2 | | 3(1.5x+9)= | | 2(3x-2)=3(4x+5)+7X | | 144x=3268.80 | | 5x-12+x=-13 | | 4/3x3.14x3.04^3 | | -4p+8(p+3)=4(p-8)+2 | | 6(x+4)-3x=11 | | f(2.5)=2x^2-3+7 | | (4x-15)+(5x+11)+(5x+5)+(6x+19)=360 | | -6.5-4x-1.6-3x=-6+9.8 | | 7(x^2)-2=5x | | 8xt=32 | | 2(5x+4)-2(9x+2)= | | 7n-(1+7n)=3(n-7)-7n | | 72x(3/2)n | | 30x^2-114x+108=0 | | n+9=25 | | 19h+1.50=15+2.75 | | (X-5)/4=-20 | | 3(w-2)-2=8-(w+4) | | 9x=12+60 | | 2450=1500+z | | 19h+1.50=15+2.75h |

Equations solver categories